Girls will be boys : cross-dressed women, lesbians, and American cinema, 1908-1934 - Horak, Laura (Rutgers University Press, 2016)
Laura Horak spent a decade scouring film archives worldwide, and what she discovered could revolutionize our understanding of gender roles in the early twentieth century. Girls Will Be Boys examines over 400 examples of women dressed as men in American films made between 1908 and 1934, revealing that Cross-Dressed women were once viewed as wholesome and used to lend respectability to the fledgling film industry.